Identification and evolution analysis of YUCCA genes of Medicago sativa and Medicago truncatula and their expression profiles under abiotic stress - Shao, An; Fan, Shugao; Xu, Xiao; Wang, Wei; Fu, Jinmin (Frontiers in Plant Science, 2023)
The YUCCAs (YUC) are functionally identified flavin-containing monooxidases (FMOs) in plants that act as an important rate-limiting enzyme functioning in auxin synthesis IPA (indole-3-pyruvic acid) pathway. In this study, 12 MsYUCs and 15 MtYUCs containing characteristic conserved motifs were identified in M. sativa (Medicago sativa L.) and M. truncatula (Medicago truncatula Gaertn.), respectively. Phylogenetic analysis revealed that YUC proteins undergone an evolutionary divergence. Both tandem and segmental duplication events were presented in MsYUC and MtYUC genes. Comparative syntenic maps of M. sativa with M. truncatula, Arabidopsis (Arabidopsis thaliana) or rice (Oryza sativa L.) were constructed to illustrate the evolution relationship of the YUC gene family. A large number of cis-acting elements related to stress response and hormone regulation were revealed in the promoter sequences of MsYUCs. Expression analysis showed that MsYUCs had tissue-specific, genotype-differential expression and differential abiotic stress response pattern based on transcriptome data analysis of M. sativa online. In addition, RT-qPCR confirmed that salt stress significantly induced the expression of MsYUC1/MsYUC10 but significantly inhibited MsYUC2/MsYUC3 expression and the expression of MsYUC10/MsYUC11/MsYUC12 was significantly induced by cold treatment. These results could provide valuable information for functional analysis of YUC genes via gene engineering of auxin synthetic IPA pathway in Medicago.